(3eSGdc GdCHUGQ aj eeGdc GdCeUGQs - (3CMeO Hf jMji Hf aVd Gddg GdbQTj GdYOhj GdYeQj, TgGH GdOjf,J (B749 (3g` s
(3ChdgG (B:s
(3Mcje GdTYQGA hTGYQ GdMceGA Jcde Ydi GdSfI GdfGS hYGUQ GdTYQGA acGfhG hGab Khd CQSWhWGdjS hhGai HCeKGd Jdc GdfhGejS s
(3BNQgG (B:s
(3ai GdSaQ GdSGOS YTQ hefge GdCOjH CHh eMeO GdMSf Hf CMeO Hf McjfG GdHZOGOi hGdMeO ddg hMOg hUdhGJg Ydi SjOfG eMeO hBdg hUMHg hSdGeg hMSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3hgPG GdeLdO jTJed Ydi JQGLe NeSjf TGYQkG hChd GdeLdO agQSJ HCSeGFge hChdge (B: (3CHh GdWjH GdeJfHi hBNQge GdTQja CHh jYdi eMeO Hf UGdM GdgGTei GdYHGSi GdeYQha HGHf GdgHGQjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B268 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B204s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1662s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs